Public Service Motivation and Employees’ Performance in a Nigerian Public Higher Institution - Folayan, Funmilayo; Alabi, Aanuoluwapo (Àgídìgbo: ABUAD Journal of the Humanities, 2023)
With constant strike actions and salaries considered to be insufficient to live a meaningful life, the general conclusion is that employees in the Nigerian public sectors are becoming unsatisfied and by implication unhappy. The dimensions of Public Service Motivation (PSM) proposed by Perry & Wise (1990) are considered a possible catalyst to manage the situation. This study seeks to examine the possible link between Public Service Motivation (PSM) mechanisms and employees’ performance using a Nigerian public Higher Institution (the Federal Polytechnic, Ado-Ekiti) as a case study. A sample size of 460 was drawn from the academic and non-academic Staff of the Federal Polytechnic Ado-Ekiti. The study used questionnaire as the research instrument and analysed the data with statistical tool of SPSS version 22.0 to extract means and standard deviation of the variables. Out of the 460 administered questionnaires, 426 were retrieved while 34 were not returned. Out of the retrieved 426 questionnaires, 408 were valid while 18 were invalid. The respond rate of the respondents to the study questionnaires was 88.69% representing an excellent grade. The mean score 2.41, 1.61, and 1.78 were accepted as a positive relationship in hypotheses testing since they are less than the set bench marked of 2.5. Consequently results of the study revealed that PSM – dimensions will have significant effect on employees’ performance if genuinely deployed. Therefore, to salvage citizens dwindling interest in the public service, and to get the best out of the present crop of employees, PSM dimensions is proposed to be inculcated into the motivation policy of the public service guide/policy.